Evaluasi “Sekolah Gratis” SMA/SMK di Kota Bandar Lampung - Ridwan Saifuddin (Balitbangda Provinsi Lampung, 2017)
The evaluation intended to determine the effect of free school policy implementation in the form of “bina lingkungan (biling)” program. The “biling” was implemented in the acceptance of new students to achieve eight National Standards of Education for the Senior High Schools/Vocational Schools in Bandar Lampung City. The evaluation was conducted with quantitative descriptive approach. Free school policies had positive and negative impacts on education units in Bandar Lampung City. The positive impacts, particularly on the achievement of compulsory education, school enrollment rates, illiteracy eradication, and challenges to school head-masters and teachers in dealing with learners with diverse academic and non-academic abilities. The negative impacts were due to the unpreparedness of the schools, both were regarding to the availability of educational facilities, teacher and educational personnels, and the school's financial capacity to implement the learning process which accommodated a broad student diversity, especially in term of academic ability.